Dongola. Seasons in 2012–2013/ Appendix: The skeletal remains from the sanctuary of Annain the Monastery on Kom H - Włodzimierz Godlewski; Robert Mahler (Polish Archaeology in the Mediterranean, 2016)
The four seasons, two in 2012 and two in 2013, carried out in ancient Dongola by an expeditionfrom the Polish Centre of Mediterranean Archaeology, University of Warsaw, were devotedto continuing excavations in a number of areas: the fortifications on the Citadel and houses from theFunj period (17th–18th century) outside of the fortifications; site SWN on the Citadel, includingBuilding B.I (Palace of Ioannes) and Building B.V (church); and the monastery complex on Kom H,encompassing the monastic church, sanctuary of Anna, gates to the monastery for monks and laity,finally the commemorative building of the Dongolan bishops with three crypts where the third ofthe crypts was revisited to study the burials from an anthropological perspective. In late 2013, a newQatar–Sudan Archaeological Project (No. 10) was launched with fieldwork concentrated on theMosque Building and within the Citadel.